Pengaruh Kompensasi, Sanksi, Lingkungan Kerja Terhadap Kinerja Karyawan Pada Home Industri Mainan Edukasi Anak Wuffyland Malang - Eka Nova Melinda; Hadi Sunaryo; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to describe the Compensation, Penalty, Work Environment and Employee Performances of the Home Industry Wuffyland of Malang Regency, to determine the effect of Compensation, Penalty, Work Environment and Employee Performances. This research was conducted at the Home Industry Wuffyland of Malang Regency with a  sample of 54 respondents. The data analysis technique uses multiple linear regression analysis. The results of the descriptive analysis showed that employees of the Home Industry Wuffyland of Malang Regency perceive agreement on all research variables, namely Compensation, Penalty, Work Environment and Employee Performances.  Compensation has a significant effect on the performance of the Home Industry Wuffyland of Malang Regency. Penalty has a significant effect on the performance of the Home Industry Wuffyland of Malang Regency. Work Environment has a significant effect on the performance of the Home Industry Wuffyland of Malang Regency. Employee Performance has a significant effect on the performance of the Home Industry Wuffyland of Malang Regency. Keywords: Compensation, Penalty, Work Environment, and Employee Performance